Epidemiological Study of Paracoccidioidomycosis and Histoplasmosis in a Suburb of San Félix City, Bolívar State, Venezuela - Cermeño, Julman; Cermeño, Julmery; Godoy, Gerardo; Hernández, Isabel; Orellán, Yida; Blanco, Ytalia; Penna, Salvador; García, Luily; Mender, Thamara; Gonsálvez, Marisa; López, César; Hernández, Neudys; et al. (Investigación Clínica, 2009)
Epidemiologic studies of deep mycosis have been scarce in Bolívar state, where paracoccidioidomycosis and histoplasmosis are considered as endemic diseases. The aim of this study was to determine paracoccidioidomycosis and histoplasmosis prevalences in people from a suburb of San Félix, Bolívar state, Venezuela. Three-hundred volunteers agreed to participate in this study and they were inoculated with paracoccidioidine and histoplasmine. Identification and epidemiologic data were registered. Reading of skin tests after 24 hours was performed in 275 persons. Paracoccidioidine test was positive in 10.2% (n=28). A higher percentage of positive reactions in the age group of 40-50 years old (n=10; 35.7%) was observed. Bricklayers, farmers and miners were positive in 27.3 % (3 out of 11), a higher percentage than in people with other occupations. Histoplasmine test was positive in 7.6% of cases (n= 21). The higher percentage of reactivity was observed in the age group of 40-50 years old (n=9; 42.9%). There was a direct proportional relationship between staying time in the locality and H. capsulatum infection mainly in persons staying in the area for more than 30 years (p